The Effect Of Suggestion Training Program In Some Element Of The Physical Fitness And Its Relationship With Digital Level In Some Track And Field Activities - Mounir, Yessar (Journal of Physical Education, 2009)
We can limited the problem of this research is that the most physical fitness activities require from our students to have a good quantity of physical fitness in order to prepare them to doing a required performance in a good or medium average at lest. Because we do not graduate a champions and that did not mean the high fitness is not always required but on the contrary as the physical fitness is very height with our students as they able to perform the activities in a best ways in the end this will reflect when we teaching others this activities and skills in a good manner and because some of the students have a shortage with (and that is a big number) some fitness elements and also the training units which agreed to learn skills and its training is not enough to develop the physical fitness element from this point the researcher has the idea to set a simple training programs which can do it in any place with simple tools and devices in a short time (simple to implemented) in a way that all students can do it in any place to improve the physical fitness elements and to know the relation between this element and the digital level (achievement ) in some track and field events. The study aimed to find the significant differences in some physical fitness elements and the digital level for some tracks and field events which agreed in this research also to know the relationship between the physical fitness elements which relied in digital level for some tracks and field events (run 110 m obstacles triple jump and discus throw). The researcher supposes that there is a significant difference between pre and post tests in some physical fitness elements and the digital level of some track and field activities which agreed in the study for the sake of the post test. Also there is a moral contact relationship between some physical fitness elements and digital level of some tracks and field events which agreed in this research. The researcher used the experimental program because it is suited to the nature of the research which was practiced on a group of students second stage in the college of Sport Education (about 18 students) they represents 50% from the specimen after achieving equivalence between the members of the researcher specimen in the variables (length, body, mass,) for the activities of run 110 m obstacles triple jump and discus throw). The experimental design includes the one group design with pre-post tests. First the experimenting pre measurements are performed and then perform the training program (9 weeks) after that the post tests performed and then account the differences between the pre and post tests to find the effectives of the experimental variable aspects and the (training program). The researcher procedure include design seven training programs which agreed by some experts and also include doing two experiments and doing the tests and pre measurement and then implemented the training programs which took (9 weeks) by (3) medium courses each one consist of (3) weeks by (3) training units weekly and (1:2) load motion wave between each medium course and training units. After finishing the training program post tests were performed using the same guidelines in the pretest and measurements the researcher reached the following conclusion: 1. The training programs obviously improved in body variable (maximum transmission speed, explosive force for arms and legs muscles, speed force for the arms and legs, abdomen muscles, flexibility of the back and legs) and the digital level in the activities of of triple jump, discus throw and run 110 m obstacles. 2. There is a moral and unmoral between some physical variables and the digital level for some tracks and field events as following: A. About the digital level in discus throw : - there is a moral contract relationship between the digital level in discus throw events and each of the variables (explosive force for the arms muscles, speed force for the legs and arms muscles) there is no moral contact relationship between the digital level in discus throw and each of (explosive force legs muscles, speed force for abdomen muscles and flexibility for the back and arches). B. About the digital level in triple jump activities : - There is a moral contact relationship between the digital level in triple jump activities and each of the variables (maximum transmission force, explosive force for the legs muscles, speed force for the legs muscles). - There is no moral contact relationship (that did not mean that there is no relationship but may be did not reach the moral level and that belong to all the variables which did not show a moral relationship) between the digital level in triple jump and each of the variables (explosive force for the arms muscles, speed force for the arms muscles, speed force for abdomen muscles, flexibility of the back and arches). C. About the digital level in 110 m for men obstacles running: - There is a moral connection relationship between digital level in 110 m running and each from the variables (maximum transmission speed force for legs muscles, speed force for abdomen muscles, flexibility of the back and legs). - There is no moral connection relationship between the digital level in 110 m obstacles running and each of the variables (explosive force for arms muscles, speed force for arms force muscles). The researcher submitted some recommendations and suggestions: 1. Confirmed to improve and take care of the physical variables which shown a moral connection relationship with the digital levels for the agreed activities in this research. 2. Doing similar studies on other physical variables and different activities. Confirmed to developing the physical aspect for students of the College of Sport and take care of training to develop physical fitness elements with teaching the skills and activities to improve the digital level and prepare our students in a good manner to be able to continues their educations with a good amount of physical fitness which help them to know the skills and activities to teach it in the future for other students aft